Formation of Multi-Walled Carbon Nanotubes by Catalytic Chemical Vapour Deposition Using Zeolite Encapsulated Nanocrystalline Cobalt Oxides - Zhao, Wei; Jai Lee, Mi; Tae Kim, Hyung; Jin Kim, Yoo; Gong, Jianghong; Jin Kim, Ik (Asian Journal of Chemistry, 2011)
High yield multiwalled carbon nanotubes (MWNTs) were synthesized on Co-suppoted faujasitetype zeolite (FAU) by catalytic chemical vapour deposition (CCVD) using acetylene as the carbon source. Well-shaped faujasite-type zeolite (FAU) octahedral crystals of a size of 15 μm were synthesized by the hydrothermal method in a mother solution which has a composition of 3.5 Na2O : Al2O3 : 2.1 SiO2 : 1000 H2O. The effect of the Co content in the zeolite crystals on the synthesis of carbon nanotubes was investigated through high resolution transmission electron microscopy (HRTEM), field emission microscopy (FESEM), thermogravimetic analysis (TGA) and Raman spectroscopy. The inner and outer tube diameters of the synthesized multiwalled carbon nanotubes were in the range of 5.7-11.6 nm and 11.0-30.2 nm, respectively. With increasing Co content supported in the zeolite template, the carbon yield showed a monotonic increasing tendency, reaching 60.4 % when the Co content was up to 11.5 wt%.